Distribution of circulating cardiac biomarkers in healthy children: from birth through adulthood. (April 2016) - Caselli, Chiara; Ragusa, Rosetta; Prontera, Concetta; Cabiati, Manuela; Cantinotti, Massimiliano; Federico, Giovanni; Del Ry, Silvia; Trivella, Maria Giovanna; Clerico, Aldo
Aim: While circulating biomarkers are critical tools for cardiovascular adult care, their relevance in childhood is unknown.Methods: We evaluated the behavior of plasma concentrations of clinically relevant cardiac biomarkers (NT-proBNP, hs-cTnI, sST2, Galectin-3) in 106 healthy children.Results: Subjects were divided into age subgroups: 24 newborns (0–30 days), 26 infants (1–12 months), 30 children (1–12 years) and 26 adolescents (13–18 years). Healthy adults were used as control. NT-proBNP (newborns: 504.3 [211.07–942.7] ng/L, median [25–75 percentiles]; infants: 200.64 [76.88–306.73]; children: 97.27 [49.24–271.80]; adolescents: 24.35 [13.14–58.83]; p < 0.001) and hs-cTnI (newborns: 9.3 [3.3–93.8] ng/L; infants: 13.8 [4.82–72.52]; children: 11.45 [4.0–48.10]; adolescents: 2.6[2.07–3.90]; p < 0.001) were highest in the first month of life, showing a decline in the next years. sST2 and Galectin-3 showed no differences.Conclusion: Changes in hs-cTnI and NT-proBNP suggest the design of age- and sex-based reference intervals that will have to be explored in a larger population.